Public health communication should be more transparent - de Barra, M; Brown, RCH (Springer Nature, 2023)
An analysis of 2,500 public-health claims reveals that organizations rarely communicate uncertainties around the benefits of behavioural change. To be ethical, public-health communication should be accurate and transparent.